The effects of public spending composition on firm productivity - Kneller, Richard; Misch, Florian (Wiley, 2014)
This paper exploits the unique institutional features of South Africa to estimate the impact of provincial public spending on firm productivity. In contrast to existing microeconomic evidence, we explore the effects of fiscal expenditures and remove the effects of revenue raising policies. Our identification strategy is based on differences in the effects of public spending across firms within the same industry and province. We show that public spending composition affects productivity depending on the capital intensity of firms, with less capital intensive firms being particularly affected. These effects appear to be robust.